2021
DOI: 10.1108/jm2-12-2020-0322
|View full text |Cite
|
Sign up to set email alerts
|

Applications of artificial intelligence and machine learning within supply chains:systematic review and future research directions

Abstract: Purpose The purpose of this study is to investigate how artificial intelligence (AI), as well as machine learning (ML) techniques, are being applied and implemented within supply chains (SC) and to develop future research directions from thereof. Design/methodology/approach Using a systematic literature review methodology, this study analyzes the publications available on Web of Science, Scopus and Google Scholar that linked both AI and supply chain from one side and ML and supply chain from another side. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 55 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…Big data can help companies analyze and figure out the motivations of their most important clients, while also providing ideas for the creation of new offerings (Mariani et al , 2018). Further evidences are found that if an integration of blockchain and other recently developed technologies like AI are used they can help in dealing with uncertainties and risks posed with supply chain uncertainties (Gohil and Thakker, 2021; (Younis et al , 2021). The rapid development, wide use and innovations in the field of Artificial Intelligence (AI) and its branches like machine learning and deep learning which deals with extracting relevant information and generating insights from data to find decisive and sustainable solutions, are not only important for every business but also becoming indispensable to communicate with the stakeholders regarding various business decisions that concern them especially in entrepreneurship (Obschonka and Audretsch, 2020; Syvänen and Valentini, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Big data can help companies analyze and figure out the motivations of their most important clients, while also providing ideas for the creation of new offerings (Mariani et al , 2018). Further evidences are found that if an integration of blockchain and other recently developed technologies like AI are used they can help in dealing with uncertainties and risks posed with supply chain uncertainties (Gohil and Thakker, 2021; (Younis et al , 2021). The rapid development, wide use and innovations in the field of Artificial Intelligence (AI) and its branches like machine learning and deep learning which deals with extracting relevant information and generating insights from data to find decisive and sustainable solutions, are not only important for every business but also becoming indispensable to communicate with the stakeholders regarding various business decisions that concern them especially in entrepreneurship (Obschonka and Audretsch, 2020; Syvänen and Valentini, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thematic analysis has been recognized as a valuable research method for exploring diverse perspectives, highlighting similarities and differences and generating unexpected insights from research participants. It has also been widely adopted in supply chain research (Riahi et al , 2021; Younis et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the decision-making process can be automated or semi-automated [38], [46]. Given the volume of information, Artificial Intelligence (AI), and particularly Machine Learning (ML), can provide solutions in integrated production management [47], predict the probable backorder products before actual sales take place [48]. Also, it can be used in optimisation, automation, and human support by handling complex problems [49]- [51].…”
Section: A Decision-making Toolsmentioning
confidence: 99%